SUSTAINABLE DEVELOPMENT GOALS AND VICTIMS OF ARMED CONFLICT: ZERO HUNGER IN IDP CAMPS IN NIGERIA - Akpoghome, Theresa U; Oyemwense, Esohe (Commonwealth Law Review Journal, 2021)
Sustainable development goals represent the world we want to see by 2030. It is the initiative of the United Nations driven by the success achieved with the millennium development goals. The sustainable development goals launched in the year 2000 is an all-inclusive strategy with the mandate to ‘leave no one behind’. The SDGs did not specifically mention IDP’s but they are captured as vulnerable groups. There is no specific framework in international law for this target group. This paper apprises sustainable development goals and victims of armed conflict and how the goals would ensure zero hunger in IDP camps in Nigeria. The paper observes that IDP’s are those who have moved away from their homes or their habitual places of residence due to several reason that ranges from conflict, abuse of human rights, generalised violence or human made disasters but have not crossed internationally recognised border, i.e. they are still within their national boundaries. The paper notes that in times of armed conflict, international humanitarian law is the primary legislation that regulates the conduct of hostilities and forbid attacks on civilian and objects indispensable to the survival of civilian. It forbids forced evacuations of civilians except on grounds of imperative military necessity. The paper observes that IHL has a lot of provisions protecting the displaced population and forbids the use of starvation as a method of warfare and has provisions reiterating the nine core SDGs that affects displaced persons in situations of armed conflict. The notes that the existing gaps in the IHL framework and posits that some provisions need further clarification but observed that the crucial problem is that States do not respect and ensure respect of the provisions of the law and have failed to disseminate the rules as widely as possible. The paper recommends that the root cause of displacement, i.e. conflict must be addressed. It further recommends that displaced persons must be included in policy decisions of government and that durable solution must be achieved for this group of persons.